2012
DOI: 10.1016/j.cor.2012.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of high throughput gene expression data

Abstract: High throughput biological data need to be processed, analyzed, and interpreted to address problems in life sciences. Bioinformatics, computational biology, and systems biology deal with biological problems using computational methods. Clustering is one of the methods used to gain insight into biological processes, particularly at the genomics level. Clearly, clustering can be used in many areas of biological data analysis. However, this paper presents a review of the current clustering algorithms designed esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(66 citation statements)
references
References 132 publications
(166 reference statements)
0
63
0
Order By: Relevance
“…Hierarchical cluster analysis 17 revealed that gene expression profile firstly distinguished patients' BM‐MSCs from normal BM‐MSCs. It then divided again by disease category (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Hierarchical cluster analysis 17 revealed that gene expression profile firstly distinguished patients' BM‐MSCs from normal BM‐MSCs. It then divided again by disease category (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…The application of data clustering for the classification of time series is usually reserved for gene expression data [Pirim et al, 2012, Liao, 2005. In this paper, we showed how useful clustering analysis can be as an exploratory tool of the parameter space of dynamical systems.…”
Section: Discussionmentioning
confidence: 99%
“…Clustering has been used in many areas of biological data analysis (Pirim et al 2012), the goal being to find structures in high-dimension data. Such structures are often multifaceted owing to the nature of the problem.…”
Section: Introductionmentioning
confidence: 99%